Penatalaksanaan Fisioterapi pada Kasus Skoliosis dengan Modalitas Infrared dan Metode Swiss Ball Exercise - Prismalia Samini Riyadi; Putra Hadi; Wanti Hasmar (Prosiding Seminar Kesehatan Nasional, 2022)
Scoliosis is an abnormal curvature of the vertebrae laterally, in addition to making the posture not straight, scoliosis can also cause back pain and make sufferers often feel tired in the spine, especially after sitting for a long time. Scoliosis is caused by congenital influences and occurs as a result of disorders due to traumatic, degenerative, or idiopathic (unknown cause). To determine the physiotherapy management of scoliosis with infrared and swiss ball exercise that can reduce pain and improve spinal posture. After six therapeutic actions with infrared and swiss ball exercise treatment at a dose of 2 times a week for 3 weeks, the results were a decrease in pain and improve spinal posture. Summary: infrared and swiss ball exercise can reduce pain and improve spinal posture.